Implementation of electronic lab notebooks (ELNs) in science laboratory classes: student response and lessons learned - Stefanie H. Chen; Christina B. Garcia; Eric Lazear; Thomas B. Lentz; Sabrina D. Robertson; Zhen Li; Carlos C. Goller (Springer, 2024)
Abstract As data and protocols are increasingly generated, accessed, and manipulated electronically, many labs are shifting to storing data in electronic laboratory notebooks (ELNs). ELNs provide clear advantages in readability, shareability, searchability, accessibility, and data security over their paper counterparts. Our interdisciplinary program implemented ELNs across several sections of our gateway molecular biology laboratory course and analyzed the impact on 384 students (13 sections total from Fall 2016 to Spring 2018) using surveys, focus groups, and grade data. We found that students prefer the electronic format, citing the ease of transitioning to lab reports and the longevity of their data. Course grades overall were not affected by the change. Based on our experience, we offer suggestions for smoothing the transition to an ELN system in undergraduate and graduate laboratory courses, including use during remote teaching.